Density and viscosity of three ionic liquids with 2, 2, 2-trifluoroethanol. (June 2023) - Yang, Fuxin; Wang, Bangju; Jiao, Yanhao; Tan, Houzhang; Wang, Xiaopo
Highlights: 2, 2, 2-Trifluoroethanol (TFE) was selected to form working pair with ionic liquid. The viscosity and density of ionic liquids with TFE were measured. The influences of TFE on the properties of ionic liquids were analyzed. The derived properties were calculated to study the interactions of binary mixture. The hard-sphere model was used to study the viscosity of binary mixture. Abstract: Due to the lower boiling point and high solubility, ionic liquids are considered as the green and environmentally friendly chemicals, and widely studied in the absorption refrigeration cycles. However, the ionic liquids always possess high viscosity. In this work, 2, 2, 2-trifluoroethanol (TFE) was selected as a solvent to reduce the viscosity of ionic liquids. The densities and viscosities of TFE with three ionic liquids were measured at atmospheric pressure and temperature in the range of 293.15–333.15 K. The effect of solvents on reducing the viscosity of ionic liquids was analyzed. The excess properties of mixtures were calculated to analyze the interaction of the binary mixtures. The hard-sphere model was used to study the viscosity of pure substances and binary mixtures to further understand the interactions between ionic liquids and TFE.